The Influence of Consumer Perception on Purchase Intention of Electric Vehicle Product in JABODETABEK - Alfitra, Fariz; Qois Urwani, Ahmad; Annisa Fahmi, Rana; Mustikasari, Faranita (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Electric vehicles (EVs) offer potential solutions to Indonesia's pollution and reliance on fossil fuels. This study integrates the Diffusion of Innovations (DOI) model and Perceived Risk Theory to examine key factors influencing EV adoption intentions in Indonesia, using data collected from 361 respondents across Jabodetabek. Employing structural equation modeling (SEM), the study analyzes how observability, compatibility, and complexity of EVs, along with perceived financial and safety risks, affect purchase intentions while brand image moderating attitude toward use to purchase intention. Results reveal that observability and compatibility enhance purchase intention, while high perceived risks reduce it. Findings suggest that promoting EV visibility and compatibility with user needs, alongside addressing risk perceptions, can support EV adoption in Indonesia.